Wireless Area Network Infrastructure Model on Gili Ketapang Island Using Open Shortest Path First Routing Protocol - Diah Ayu Retnani Wulandari; Yudha Alif Auliya; Antonius Cahya Prihandoko; Slamin Slamin; Mohammad Zarkasi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2022)
This study aims to model the network for the archipelago and tourism on Gili Ketapang. The network model implemented is a wireless WAN network infrastructure to meet the needs of a reliable tourist area. This model implements DHCP and OSPF as the routing protocol. The methodology used is to perform simulations using a packet tracer in designing the network through several scenarios with parameters for assessing delay and packet loss. At the time of implementation, it began with a cluster area with the parameters of the number of business units spread across each hamlet. This network design utilizes OSPF, DHCP, and wireless network infrastructure resulting in the most considerable delay of 0.021 and packet loss of less than 3% so that it is included in the excellent category. The implementation results using the OSPF routing protocol, several paths do not go through the shortest path because they have to go through the backbone area, but because OSPF is a link-state, the cost is meager than the shortest path.